Perbedaan Hasil Belajar Kognitif Geografi Siswa Menggunakan Media Pembelajaran Kahoot! dengan PowerPoint - Rani Septianti Putri; Muhammad Zid; Oot Hotimah (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the difference in cognitive learning outcomes of tenth-grade geography students using Kahoot! and PowerPoint learning media at SMAN 113 Jakarta. The research adopts a quantitative design employing a quasi-experimental method with Pre-test and Post-test. The research sample was selected using purposive sampling, where samples were chosen based on specific considerations and criteria, such as the average scores of the first-semester PAS (School-Based Assessment) with an equal number of students. The samples used in this study were Class X-2 as the experimental group using Kahoot! learning media and Class X-1 as the control group using PowerPoint learning media. Data analysis techniques included instrument testing, analysis of prerequisite tests, N-Gain tests, and hypothesis testing. The test results indicated that the instruments were valid and reliable, and the data were normally distributed and homogeneous. The test of two means (Independent Sample T-test) showed that the Post-test results of the experimental and control groups obtained a significant level of 0.003, meaning that H0 was rejected and Ha was accepted as it met the testing criteria, i.e., Sig. < 0.05. This indicates that there is a difference in cognitive learning outcomes among students using Kahoot! and PowerPoint media during the geography learning process. This difference can be observed from the increase in the Post-test scores of the experimental group by 31% and the control group by 21%, supported by N-Gain test data showing the effectiveness percentage of Kahoot! media at 60% (sufficiently effective) and PowerPoint media at 39.5% (ineffective).